SISTEM INFORMASI DALAM MENDUKUNG KEMATANGAN PLANNING SMART CITY E-GOVERNMENT UNTUK PENINGKATAN KAPABILITAS PELAYANAN PEMERINTAH LOMBOK TIMUR TERHADAP MASYARAKAT - Marcho Oknivan Tumbade (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Technological developments continue to grow rapidly and the central government's goal is to achieve smart cities in Indonesia, thus demanding local governments to be able to optimally support smart cities in various regions in Indonesia, especially the East Lombok government. In the implementation of Smart City E-Government Information systems are indeed not easy when implementation will certainly collide with several social factors even with the availability of infrastructure owned by the region, several strategies are needed when in implementing Smart City there are several strategic steps that are needed to see the benchmark of regional readiness and the government based on the guidebook for the preparation of the MasterPlan Smart City 2007: Structure, Infrastructure, and Superstructure which then determines a strategy using the SWOT analysis method to support the government in evaluating and preparing to support work programs then the TOGAF approach method which after analyzing and evaluating this approach is the preparationinformation design Smart City is expected with this solution that is able to be the basis when preparing planning the East Lombok government Smart City based on the references used in writing. It is expected to be able to support the preparation of quality human resources, fulfill regional infrastructure and use technology so as to improve integrated services to the community.